Adapting to HIV: The Paradoxes of Autonomy and Vulnerability Among Young People Living with HIV in Tororo District, Eastern Uganda - A Qualitative Study - Ikwara EA; Isiko I (HIV/AIDS: Research and Palliative Care)
Emmanuel Asher Ikwara,1 Isaac Isiko2 1Child Health & Development Centre, School of Medicine, College of Health Sciences, Makerere University, Kampala, Uganda; 2Department of Community Medicine, Axel Pries Institute of Public Health and Biomedical Sciences, Nims University, Jaipur, Rajasthan, IndiaCorrespondence: Emmanuel Asher Ikwara, Email asheremmaikwara@gmail.comBackground: HIV is a significant public health issue in Uganda, particularly among young people (15– 24 years), with an estimated 150,000 living with the virus. This study examines the paradoxes of autonomy and vulnerability experienced by young people living with HIV (YPLHIV) in Tororo District, Uganda. It explores how stigma, social support, and healthcare systems shape their experiences, influencing both their autonomy and vulnerability.Methods: This qualitative study in Tororo District explored the autonomy and vulnerability of young people living with HIV, using 18 in-depth interviews and 3 focus group discussions to examine personal, social, and healthcare influences.Results: Findings reveal how stigma, social isolation, and dependence on family support impact autonomy. Participants highlighted the importance of peer support, healthcare empowerment, and resilience in managing HIV. While struggling with medication adherence and gendered expectations, many expressed a desire for independence while acknowledging the critical role of support systems in maintaining their well-being.Conclusions and Recommendations: This study explores the tension between autonomy and vulnerability among young people living with HIV in Uganda, emphasizing the roles of stigma, social support, and healthcare providers. Recommendations include stigma reduction, peer support integration, and family involvement in care.Keywords: HIV, autonomy, vulnerability, stigma, young people, peer support, social support